Research trends review on RSA scheme of asymmetric cryptography techniques - Mohd Saiful Adli Mohamad; Roshidi Din; Jasmin Ilyani Ahmad (Institute of Advanced Engineering and Science, 2021)
One of the cryptography classifications is asymmetric cryptography, which uses two different keys to encrypt and decrypt the message. This paper discusses a review of RSA scheme of asymmetric cryptography techniques. It is trying to present the domains of RSA scheme used including in public network, wireless sensor network, image encryption, cloud computing, proxy signature, Internet of Things and embedded device, based on the perspective of researchers’ effort in the last decade. Other than that, this paper reviewed the trends and the performance metrics of RSA scheme such as security, speed, efficiency, computational complexity and space based on the number of researches done. Finally, the technique and strengths of the proposed scheme are also stated in this paper.